The legal framework of English feudalism : the Maitland lectures given in 1972 / S.F.C. Milsom. - Milsom, S. F. C. (Stroud Francis Charles), 1923- (Cambridge studies in English legal history., 1976)
Professor Milsom works out a fresh view of the beginnings of the common law concerning land. The received picture depends upon progressive assumptions: key words began with their later meanings; the law began with abstract ideas of property; a tenant's title to his tenement was never subject to his lord's control; the lord had no discretion, only the power to decide disputes according to external criteria; jurisdiction in that sense was all the lord lost as royal remedies developed; and all the tenant gained was better protection of unaltered rights. It is a picture of procedural changes taking place against an unchanging background, with the feudal structure at the beginning almost as insubstantial as it was to be at the end.